Reconstructing Character Education through Islamic Religious Education in the Post-Pandemic Era: Educational Perspectives from Bangladesh - Rajarshi Dasgupta (https://ejournal.insuriponorogo.ac.id/, 2024)
The COVID-19 pandemic significantly disrupted educational systems worldwide and created profound social, emotional, and moral challenges affecting students’ character development. Prolonged school closures, social isolation, increased digital exposure, weakened social interaction, emotional instability, and educational inequalities have contributed to concerns regarding declining discipline, responsibility, empathy, and moral awareness among students. In Bangladesh, where Islamic values remain influential in educational and social life, Islamic Religious Education (IRE) presents meaningful opportunities for reconstructing character education in the post-pandemic era. This study explores the role of Islamic Religious Education in rebuilding students’ character and strengthening moral values within educational settings in Bangladesh following the pandemic. Using a qualitative literature review approach, the study examines scholarly literature related to character education, Islamic Religious Education, post-pandemic learning, and student moral development. The findings indicate that Islamic Religious Education contributes positively to reconstructing character through moral habituation, spiritual guidance, ethical reflection, emotional resilience, discipline, empathy, and community-oriented learning. Islamic teachings emphasizing honesty (sidq), responsibility (amanah), patience (sabr), compassion (rahmah), and social solidarity provide important foundations for rebuilding students’ moral competence after educational disruption. However, challenges remain, including digital dependency, weakened social engagement, teacher preparedness, curriculum adaptation, and unequal educational access. The study concludes that Islamic Religious Education can play an important role in reconstructing character education in Bangladesh when supported by curriculum innovation, teacher development, family involvement, and contextually responsive educational strategies.